2011
DOI: 10.1111/j.1469-0691.2011.03460.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the emerging role of oral spirochaetes in periodontal disease

Abstract: Spirochaetes are prominent in the polymicrobial infections that cause periodontal diseases. Periodontitis is a chronic inflammatory condition of the periodontium, characterized by proinflammatory soft tissue damage and alveolar bone loss. Treponema denticola is the most well-understood oral spirochaete, expressing a wealth of virulence factors that mediate tissue penetration and destruction as well as evasion of host immune responses. This review focuses on emerging knowledge of virulence mechanisms of Trepone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 149 publications
(179 reference statements)
0
51
0
5
Order By: Relevance
“…micra, and adherence levels to F. nucleatum similar to those of T. denticola. These results provide an in vitro basis for the findings that T. denticola is almost always found associated with P. gingivalis in vivo, while T. vincentii is isolated from subgingival microbial communities (Siqueira & Rôças, 2004;Visser & Ellen, 2011) but not necessarily associated with P. gingivalis or with periodontal disease. Overall, T. vincentii appeared to have a less adherent phenotype than T. denticola.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…micra, and adherence levels to F. nucleatum similar to those of T. denticola. These results provide an in vitro basis for the findings that T. denticola is almost always found associated with P. gingivalis in vivo, while T. vincentii is isolated from subgingival microbial communities (Siqueira & Rôças, 2004;Visser & Ellen, 2011) but not necessarily associated with P. gingivalis or with periodontal disease. Overall, T. vincentii appeared to have a less adherent phenotype than T. denticola.…”
Section: Discussionmentioning
confidence: 87%
“…Spirochaetes are detected in most samples of subgingival plaque microbiota taken from subjects with a range of periodontal conditions (Paster et al, 2001;Colombo et al, 2009;Visser & Ellen, 2011). T. denticola has been the most frequently isolated and best-characterized oral spirochaete (Moore et al, 1982;Riviere et al, 1992), but it is evident that multiple phylotypes are found in individual subjects (Dewhirst et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the reduced virulence can be due to the synergistic effects of defective motility, chemotaxis, and biofilm formation in the Td⌬214 mutants. T. denticola produces numerous virulence factors involved in cytotoxicity, adherence, invasion, and immunomodulation (38,39). Alternatively, TDE0214 may also affect the pathogenicity of T. denticola via other virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…These organisms are among the last few as-yet-uncultured major human pathogens. Similarly, among the numerous Treponema phylotypes found in the oral cavity, only 10 different species have been cultivated, with Treponema denticola being the most extensively studied (122). The development of an axenic culture of pathogenic Treponema remains a challenge for microbiologists.…”
Section: Spirochetesmentioning
confidence: 99%